Measuring prison climate across contexts: lessons from administering the Prison Climate Questionnaire in the USA - Tiem, Britte van (European journal of criminology, 2025)
Prison climate surveys are uniquely positioned to identify how the quality of prison life differs both within and between institutions. However, much of this comparative potential remains unrealized, in part because of insufficient evidence that existing survey instruments are suitable for use in different contexts and that survey data can be reliably compared across contexts. In this paper, we explore the suitability of the Prison Climate Questionnaire (PCQ), originally developed in the Netherlands (NL), for use in the USA by assessing its factor structure, reliability, construct validity, and criterion validity using survey data from Pennsylvania (N = 632). We compare our findings with previously published psychometric results from the NL. Results of psychometric analyses show several striking similarities between the two countries, pointing to areas where the survey might be improved. While the PCQ shows potential for stand-alone use in the USA, further work would be required to use the tool in explicitly comparative research. We draw lessons from this collaboration to inform future efforts to develop standardized prison climate surveys more suitable for comparative analyses of prison climate in Europe and beyond.